Analysis of the Utilization of the Case Management System Model at the Intelligence Directorate of the Densus 88 Anti-Terror Unit, Indonesian National Police - Ramadhany, Gilang Perdana; Handayani, Riska Sri; Badry, Ahmad Ibrahim (International Journal of Social Science and Community Service, 2026)
Integrated data management has become critical for intelligence analysis, particularly in terrorism-related crime handling. The Intelligence Directorate of Detachment 88 AT Polri faces significant challenges managing case data from multiple units and information sources. This study analyzes the utilization of a Case Management System (CMS) model in supporting intelligence analysis activities at Detachment 88. A qualitative approach was employed through in-depth interviews with key informants (Director of Intelligence, Head of Sub-Directorate of Analysis, and intelligence analysts) and document analysis of internal reports and national policies conducted during 2020-2023. Findings indicate that integrated CMS implementation positively impacts analysis speed, information accuracy, and cross-unit coordination. However, limitations persist including partial data integration due to format differences, reliance on manual verification processes, slow processing of large-volume data from social media and CCTV, and network infrastructure constraints in operational areas. System interoperability plays a crucial role in supporting timely and precise intelligence decision-making. The study identifies three critical pillars for CMS effectiveness: multi-source data integration, adaptation to evolving terrorism methods utilizing digital technology, and robust data security mechanisms including encryption and role-based access controls. CMS must evolve from a data repository to an AI-enabled analytical platform with automated data fusion, modular architecture, and layered security protocols to effectively counter dynamic terrorism threats while maintaining strict confidentiality standards.